PARIWISATA KREATIF DAN KEGIATAN EKSTRAKURIKULER BERBASIS BAMBU DALAM PENGEMBANGAN MODEL BISNIS CV SURATIN BAMBOO - Dewa Ayu Tenara Kardinia Cidhy; Lukman M. Baga; Setiadi Djohar (School of Business, Bogor Agricultural University (SB-IPB), 2016)
The objective of this study was to design a prototype of a future business model which would be adopted to achieve balance between the aspects of new business opportunities and competitive advantages of CV Suratin Bamboo. The analytical method utilized in the study was the business model canvas approach (BMC) supported by the blue ocean strategy and SWOT. The results revealed that through this business model development, bamboo workshop is expected to provide information regarding bamboo derived products, raise awareness of preserving the indigenous bamboo culture, increase sense of belonging to domestic products, as well as become the primary support of innovation and ideas in constructing Indonesia as a nation. Meanwhile, for businesses actors, besides increasing revenue, conducting bamboo workshops is expected to increase the company growths for the long term. The opportunity to maneuver in the development of bamboo-based business model demonstrates that bamboo business with high quality products has both tangible and intangible potentials to be developed further.Keywords: bamboo, blue ocean strategy, business model canvas, creative tourism, extracurricularABSTRAKTujuan penelitian ini adalah merancang prototype model bisnis masa depan yang akan digunakan untuk menemukan keseimbangan antara aspek peluang bisnis yang baru dan aspek keuntungan kompetitif CV Suratin Bamboo. Metode analisis yang digunakan adalah dengan pendekatan kanvas model bisnis (BMC) dilengkapi dengan blue ocean strategy serta SWOT. Hasil penelitian menunjukkan melalui pengembangan model bisnis ini, pelatihan bambu diharapkan mampu memberikan informasi tentang produk turunan bambu, meningkatkan kesadaran melestarikan kearifan lokal budaya bambu, meningkatkan rasa cinta produk dalam negeri, serta menjadi pendorong lahirnya inovasi dan gagasan yang membangun bangsa Indonesia. Sementara bagi pelaku usaha, selain peningkatan revenue, pelatihan bambu diharapkan mampu meningkatkan pertumbuhan perusahaan untuk jangka panjang. Peluang bermanuver dalam pengembangan model bisnis berbasis bambu menunjukkan bahwa bisnis bambu dengan produk yang baik bersifat tangible dan intangible sangat potensial untuk terus dikembangkan. Kata kunci: bambu, blue ocean strategy, kanvas model bisnis, pariwisata kreatif, ekstrakurikuler